2016
DOI: 10.3390/molecules21050674
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Cu(II), Pd(II) and Pt(II) Complexes with 8-Ethyl-2-hydroxytricyclo(7.3.1.02,7)tridecan-13-one-thiosemicarbazone: Antimicrobial and in Vitro Antiproliferative Activity

Abstract: New Cu(II), Pd(II) and Pt(II) complexes, (Cu(L)(H 2 O) 2 (OAc)) ( 1 ), (Cu(HL)(H 2 O) 2 (SO 4 )) ( 2 ), (Cu(L)(H 2 O) 2 (NO 3 )) ( 3 ), (Cu(L)(H 2 O) 2 (ClO 4 )) ( 4 ), (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…These results displayed that the metal ions play a significant part in the interaction with separated DNA, so we could conclude that the compound minimizes the growth of the pathogenic organism through interaction with genome. Our results revealed that partial binding to DNA was observed by VO (II) and Pd (II) imine metal chelates …”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…These results displayed that the metal ions play a significant part in the interaction with separated DNA, so we could conclude that the compound minimizes the growth of the pathogenic organism through interaction with genome. Our results revealed that partial binding to DNA was observed by VO (II) and Pd (II) imine metal chelates …”
Section: Resultssupporting
confidence: 62%
“…The viscosity measurements show that all the as‐prepared metal complexes intercalate between adjacent CT‐DNA base pairs, giving rise to lengthening of the DNA double helix and an increase in viscosity, as shown in Figure . The results suggest that all the metal‐imine complexes intercalate with the adjacent base pairs, thereby causing lengthening of the DNA helix, which facilitates the intercalation mode of CT‐DNA with the as‐prepared metal‐imine complexes …”
Section: Resultsmentioning
confidence: 93%
“…calcd for C 12 2.3 | General procedure for the preparation of the metal complexes (1)(2)(3)(4)(5)(6)(7)(8)(9) All the new metal complexes 1-9 were prepared by the direct reaction between the ligand and the corresponding metal salts. : 142-144°C; yield (83%); FW: 249.332 g mol −1 .…”
Section: Synthesis Of 2hydroxybenzaldehyde-4-allyl-smethylisothiosementioning
confidence: 99%
“…Abs control -Abs sample À Á =Abs control À Á ·100: (9) were synthesized in ethanol in good yield. Single crystals were obtained for six coordination compounds (3), (5-9) and ligand HL·HI·C 2 H 5 OH with recrystallization from various solvents, such as DMSO, DMF, methanol, ethanol, chloroform, and their structures found using X-ray analysis.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation